Impacts of Monetary Policy on Inflation in Bangladesh - Abdullah, Mohammad Nayeem; Parvez, Kamruddin; Tooheen, Rahat Bari (Global Disclosure of Economics and Business, 2012)
The objective of this paper is to analyze and discuss the impacts of monetary policy on Bangladesh inflation, identify the major drawbacks of the policies in minimizing the inflation rate and suggest policy recommendations on some key issues of Bangladesh inflation. To estimate the effects of the monetary policy in Bangladesh, at first the impact of different monetary policy tools used by the “Central Banks” of the developed countries have been reviewed. Next, the impact of the monetary policy of Bangladesh Bank and government have been analyzed for which the data on money supply, growth of the GDP, changes in the price level, and changes in the unemployment rate have been quantitatively analyzed. We mainly used Consumer Price Index to determine the level on inflation in Bangladesh. Moreover, our study focuses on data collected from the 1950-2012, mainly focusing our study from the period of 2000-2012 as major transitions have been observed in the economy during the 12 years. We have further analyzed whether there is any correlation between (i) inflation rates and money supply, and (ii) inflation rates and growth of GDP. On the basis of the outcome of the qualitative and quantitative analysis, in the end findings and conclusion have been drawn. We have found the correlation, the impacts of monetary policy and inflation, their drawbacks and possible solutions such as independence of the monetary policy from the fiscal policy and enhancing the transparency, communication and signaling effect of policy moves, keeping the broad money in line with the estimated real GDP growth, borrowing from non-bank sources, and control money supply through various open market operations. Due to lack of access to sufficient data, some of our work is based on hypothesis and models. So some data vary according to the model being used. Lastly, even though, many works have been done from the perspective of developed and other developing countries, much work has not been carried out to establish the relationship between monetary policy and inflation in Bangladesh.GEL Classification Code: E31; E42; E50